IMPLEMENTASI PERATURAN DAERAH KABUPATEN BUNGO NOMOR 16 TAHUN 2012 TENTANG RETRIBUSI PARKIR DI TEPI JALAN UMUM (Studi pada Dinas Perhubungan Kabupaten Bungo) - Nanang Al Hidayat; Burhanuddin Burhanuddin; Asra'i Maros (Jurnal Administrasi Sosial dan Humaniora, 2022)
Based on the initial observations of researchers in the field, several problems can be identified in the implementation of the Bungo Regency Regional Regulation Number 16 of 2012 concerning Parking Fees on Public Roads, namely the target of receiving fees is not achieved 100%; The determination of the Revenue and Revenue Budget is out of sync between the Revenue Service and the Transportation Service; Limited Human Resources for Transportation in Oversight of Parking Attendant Performance Activities. The purpose of this research is to find out the implementation of Bungo Regency Regional Regulation No. 16 of 2012 concerning Parking Fees on Public Roads. The method chosen in this study is a descriptive method with a qualitative approach. The population in this study were all employees of the transportation service, and people who use parking services in Bungo Regency with a sample of 12 people. The results showed that the Implementation of Bungo Regency Regional Regulation Number 16 of 2012 concerning Parking Fees on Public Roads was seen from 4 main issues, namely parking locations, services, obligations and prohibitions, and rates. The results of the study show that the Bungo Regency Regional Regulation Number 16 of 2012 has not been fully implemented by parking attendants or parking service users themselves.